PENGENALAN POLA SUARA MANUSIA BEREKSTENSI FILE WAV MENGGUNAKAN METODE FAST FOURIER TRANSFORM DAN BAYES - Nurlia Apriani; Rita Wiryasaputra; Lastri Widya Astuti (Computatio : Journal of Computer Science and Information Systems, 2018)
The human voice is a very unique sound wave. That's because every human being has a different kind of sound wave. The fundamental difference in human voice is high the low the sound level associated with the signal from sound waves. The purpose of this research is to know the accuracy result from Fast Fourier Transform and Bayes method in pattern recognition. The Fast Fourier Transform method is used for feature extraction and Bayes method is used to calculate the sound probability value between the train data and test data, then Bayes Method is used to determine the result of the introduction of some previously stored train data. This research was made using Matlab R2016a, by matching the pattern of human sound that has been made before or called train data with new sound pattern or called test data. Testing is done on voice in the database and the voice is not in the database. Test results for voice in the database were 96% for first men and 76% for first women. While testing for voice is not in the database is 46% for second men and 50% for second women